Pergeseran Pembagian Harta Warisan Pada Masyarakat Pakpak di Desa Sukamakmur Kecamatan Gunung Meriah Kabupaten Aceh Singkil - Rasi Dewinta Berutu; Harisan Boni Firmando; Wensdy Sitindaon; Roida Lumbantobing; Elvri Teresia Simbolon (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study is entitled the distribution of inheritance in the Pakpak community in Sukamakmur Village. Gunung Meriah District, Aceh Singkil Regency, namely the distribution of inheritance in the past and present communities with the aim of knowing 1) The shift that occurred in the distribution of inheritance in the Pakpak community in Sukamakmur Village. 2) The factors behind the shift in the distribution of inheritance in the Pakpak community in Sukamakmur Village. The method used in this study is a descriptive qualitative research method, to understand what phenomena are experienced by the research subjects holistically, namely by describing them in words and language, based on the findings in the field. The results of the study show that the distribution of inheritance in the Pakpak community in Sukamakmur Village has shifted where in the past, the community in implementing inheritance drew a patrilineal system which drew the father's lineage so that the inheritance that was entitled and became the heir of the son so that parents prioritized sons in inheritance while if the Pakpak community drew a patrilineal lineage, of course the position and even the rights of daughters to get it were very non-existent, while at present the Pakpak community in Sukamakmur Village parents provide opportunities so that parents on average give their property to their daughters. Now the Pakpak community carries out inheritance in the past parents were required to present Kula-kula, Senina, Berru but what happened in the village was that some people no longer followed to present these three, in that community only distributed inheritance among themselves between parents and children only